2016
DOI: 10.15407/ubj88.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Ca(2+)-dependent regulation of the Ca(2+) concentration in the myometrium mitochondria. I. Trifluoperazine effects on mitochondria membranes polarization and [Ca(2+)](m)

Abstract: Са2+-dependent regulation of Ca2+ exchange in mitochondria is carried out with participation of calmodulin. We have shown previously that calmodulin antagonists reduced the level of mitochondrial membrane polarization and induced increase of the ionized Са concentration in both the mitochondrial matrix and cell cytoplasm. The concentration-dependent influence of trifluoperazine on the level of polarization of mitochondrial membranes has been shown in this work. The coordinates of the Hill graphs were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
2
0
2
Order By: Relevance
“…We have shown previously that calmodulin antagonists caused depolarization of mitochondrial membranes and an increase of the ionized Са concentration in both the mitochondrial matrix and the cell cytoplasm [9]. At the first part of this paper we have shown the concentration-dependent influence of calmodulin antagonist trifluoperazine on the level of mitochondrial membranes polarization with k 0.5 24.4 ± 5.0 μM and the Hill coefficient 2.0 ± 0.2 [10]. But it was also shown that preincubation of isolated mitochondria in mediums of different composition with 25 μM trifluoperazine did not affect the [Ca 2+ ] m values both before and after the addition of 100 μМ Са 2+ .…”
mentioning
confidence: 67%
“…We have shown previously that calmodulin antagonists caused depolarization of mitochondrial membranes and an increase of the ionized Са concentration in both the mitochondrial matrix and the cell cytoplasm [9]. At the first part of this paper we have shown the concentration-dependent influence of calmodulin antagonist trifluoperazine on the level of mitochondrial membranes polarization with k 0.5 24.4 ± 5.0 μM and the Hill coefficient 2.0 ± 0.2 [10]. But it was also shown that preincubation of isolated mitochondria in mediums of different composition with 25 μM trifluoperazine did not affect the [Ca 2+ ] m values both before and after the addition of 100 μМ Са 2+ .…”
mentioning
confidence: 67%
“…Mitochondria, loaded with a fluorescent probe, were incubated without (control) or with 10 µM calix [4]arenes during 5 min in Mg 2+ -or Mg 2+ ,ATP-containing medium in the absence of exogenous Ca 2+ . As we have shown previously , ATP addition to the Mg 2+ -containing medium resulted in [Ca 2+ ] m (in the absence of exo genous Ca 2+ ) [28] and total Са 2+ accumulation increase [27]. The results of each experiment were normalized to 100% of the control sample.…”
Section: The Effect Of Calix[4]arenes с-1012 с-1021 с-1023 с-102mentioning
confidence: 99%
“…Ó попередніх роботах ми показали, що введення АТР до середовища інкубації, що містить Mg 2 , супроводжується зростанням рівня ендогенного Са у матриксі мітохондрій [17] та істотно збільшує загальний рівень акумуляції Са 2 у цих структурах [16]. Отже наступну серію експериментів ми провели у середовищі, що містить Mg 2+ ,АТР.…”
Section: результати та обговоренняunclassified
“…Цікавим є той факт, що калікс [4]арени з більшою ефективністю проявили себе у середовищі, що містить Mg 2+ , АТР. Íаші попередні результати показали, що за таких умов мітохондрії мають найбільшу Са 2 -акумулюючу активність, що супроводжується як зростанням загального рівня накопичення Са 2+ [16], так і його йонізованої форми [17].…”
Section: результати та обговоренняunclassified